2015
DOI: 10.1109/jstars.2015.2437896
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural Network Model Function (AMF) for SARAL-Altika Winds

Abstract: High-quality winds over the ocean surface, at an enhanced spatio-temporal resolution are required for a better understanding of the dynamics of the ocean and atmosphere. Altimetry helps in increasing the frequency of satellite observations. Traditional algorithms for wind speed retrievals from altimeter consider only the backscatter (sigma-0) and possibly the significant wave height (SWH). In this study, we propose an artificial neural network (ANN) model function for AltiKa on board Satellite for ARgos and AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The training epoch stops when the error converged to the minimum. Many studies have applied ANN for normal conditions U 10 estimation (Ali et al, 2015;Gourrion et al, 2002;Jiang et al, 2020), but challenging data filtering and extensive training samples requirement limit the ANN for U 10 tropical cyclone application.…”
Section: Multiple Parameter Modeling and The Accuracy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The training epoch stops when the error converged to the minimum. Many studies have applied ANN for normal conditions U 10 estimation (Ali et al, 2015;Gourrion et al, 2002;Jiang et al, 2020), but challenging data filtering and extensive training samples requirement limit the ANN for U 10 tropical cyclone application.…”
Section: Multiple Parameter Modeling and The Accuracy Assessmentmentioning
confidence: 99%
“…The recent altimeter missions with radiometers onboard provide simultaneously brightness temperatures (T b ) that can be used to estimate this response to the signal. Integrating the T b in U 10 model have improved the accuracy of altimeter U 10 in low-to-moderate wind (Ali et al, 2015;Bushair & Gairola, 2019;Jiang et al, 2020), and scatterometer U 10 inside the tropical cyclone (Stiles et al, 2014;Xu et al, 2018). Lillibridge et al (2014) reported an improved accuracy of SARAL Ka-band U 10 when integrating atmospheric parameters such as pressure, temperature, water vapor, and liquid water content.…”
mentioning
confidence: 99%
“…This non-dynamic numerical model has been used in many oceanographic [10][11][12][13][14][15] (and meteorological studies [16][17][18]. The ANN technique is also useful for satellite-parameter retrievals [19][20][21][22]. Multiple linear regression (MLR) is a method dealing with linear dependencies, whereas neural networks deal with nonlinearities.…”
Section: Introductionmentioning
confidence: 99%
“…This non-dynamic numerical model has been used in many oceanographic ( (Liu et al, 1997, Sharma and Ali., 2012. This technique is also found useful for satellite parameter retrievals (Krasnopolsky and Schiller., 2003, Ali et al, 2015, Sharma et al, 2013, Ali et al, 2016. ANN requires three sets of data, one for training, one for veri cation and the other for validation.…”
Section: Introductionmentioning
confidence: 99%